THE FEMINIST MEMOIR PROJECT: VOICES FROM WOMEN'S LIBERATION - Ekawati Marhaenny Dukut (Celt: A Journal of Culture, English Language Teaching & Literature, 2002)
Edited by RACHELBLAU DUPLEISIS and ANN SNITOW U.S.A. : Three River Press 1998, 531pp ISBN: 0-609-80384-0 Reviewed by EKAWATI MARHAENNY DUKUT